A network analysis of DSM-5 posttraumatic stress disorder symptoms and correlates in U.S. military veterans. (January 2017) - Armour, Cherie; Fried, Eiko I.; Deserno, Marie K.; Tsai, Jack; Pietrzak, Robert H.
Highlights: We used a nationally representative sample of trauma-exposed military veterans (NHRVS) and selected 221 who reported clinically significant DSM-5 PTSD symptoms. We estimated two networks; a DSM-5 PTSD network and a DSM-5 PTSD network with clinically significant covariates. The networks revealed that symptoms were positively connected with especially strong connections emerging between several items. Incorporation of clinically relevant covariates into the PTSD network revealed paths between PTSD's symptom of self-destructive behavior and suicidal ideation amongst others. Abstract: Objective: Recent developments in psychometrics enable the application of network models to analyze psychological disorders, such as PTSD. Instead of understanding symptoms as indicators of an underlying common cause, this approach suggests symptoms co-occur in syndromes due to causal interactions. The current study has two goals: (1) examine the network structure among the 20 DSM-5 PTSD symptoms, and (2) incorporate clinically relevant variables to the network to investigate whether PTSD symptoms exhibit differential relationships with suicidal ideation, depression, anxiety, physical functioning/quality of life (QoL), mental functioning/QoL, age, and sex. Method: We utilized a nationally representative U.S. military veteran's sample; and analyzed the data from a subsample of 221 veterans who reported clinically significant DSM-5 PTSD symptoms. Networks were estimated using state-of-the-art regularized partial correlation models. Data and code are published along with the paper. Results: The 20-item DSM-5 PTSD network revealed that symptoms were positively connected within the network. Especially strong connections emerged between nightmares and flashbacks; blame of self or others and negative trauma-related emotions, detachment and restricted affect; and hypervigilance and exaggerated startle response. The most central symptoms were negative trauma-related emotions, flashbacks, detachment, and physiological cue reactivity. Incorporation of clinically relevant covariates into the network revealed paths between self-destructive behavior and suicidal ideation; concentration difficulties and anxiety, depression, and mental QoL; and depression and restricted affect. Conclusion: These results demonstrate the utility of a network approach in modeling the structure of DSM-5 PTSD symptoms, and suggest differential associations between specific DSM-5 PTSD symptoms and clinical outcomes in trauma survivors. Implications of these results for informing the assessment and treatment of this disorder, are discussed.